System Tasks of a Doctoral Dissertation - Lulanski, Pano (Research Papers, 2015)
The study of the system tasks of a doctoral dissertation is a topical issue for the research advancement of the contemporary knowledge-based economy.The purposeof the present study is to understand the basic system components and links in the research guidance of doctoral students for writing their dissertation thesis (PhD research, writing and defense), such as mentoring procedures, primary systematization of work activities, research structure and so on, and to indicate their place and role in the doctoral research process.The research objectof the paper covers the PhD student processes in all phases of the PhD training (mentoring, research, writing and defense of a dissertation), whilethe research subject of the paper is the extrapolation of the general content of selected basic system links of the doctoral dissertation. The analysis includes the followinghighlights: a) system tasks in doctoral training; b) primary systematization of the PhD thesis; c) system positioning of the research structure; d) main system tasks of the doctoral student activities; e) composition of the doctoral thesis; f) systematic functional technology of the research completion; g) the scientific character as a strategy for successful PhD research and defense.JEL:A20, B41,C42, C82